A Survey on Factors Influencing Dysmenorrhea Among Women in Kanchipuram District Tamil Nadu - M, Balachandar; .J, Selvanathan; B, Revathi.; H, Sivanesh; D, Stephenraj,; Raj. R, Azhagu (Journal of Neonatal Surgery, 2025)
Dysmenorrhea, a prevalent gynecological disorder characterized by painful menstrual cramps, often signals dysfunction within the hypothalamic-pituitary-ovarian axis and may be associated with pelvic inflammation. It significantly affects the quality of life of young women and is influenced by various lifestyle, nutritional, and psychological factors . This study aimed to evaluate the prevalence and severity of dysmenorrhea among college-aged women aged (19-26) years in Kanchipuram District, Tamil Nadu, and to identify the contributing factors such as dietary habits, sleep patterns, stress, skipping breakfast, part-time jobs, sleeping, genetic factors, being an athlete, age, profession, being vegetarian or non-vegetarian, fruit intake, fast food consumption, junk food consumption, age at first menstruation, having regular or irregular periods, and use of painkiller drugs were examined for their influence on dysmenorrhea among college students in Tamil Nadu. Data were collected by a self-administered questionnaire contains the demographic variables, menstrual history, severity of dysmenorrhea, and associated lifestyle factors including breakfast habits, fast food consumption, physical activity, and family history. Menstrual patterns were analyzed manually and with statistical tools. The results revealed that menstrual patterns in college going students were abnormal (41%) irregular periods (22%) and abnormal in bleeding (76%) were recorded. The present study concludes that the various factors like, skipping breakfast, food quality, part time job, sleeping, mental stress, fast food, junk food, and anemia were influencing Dysmenorrhea. The findings suggest that poor dietary habits, particularly breakfast skipping and fast-food intake, along with other modifiable lifestyle factors, are strongly associated with the prevalence and severity of dysmenorrhea. Health education and intervention programs focusing on nutrition and menstrual hygiene awareness are essential to improve reproductive health and quality of life among young women.